PENGEMBANGAN ALAT PERAGA PNEUMATIK OTOMATIS BERBASIS PLC DAN PENDAMPINGAN PENGGUNAANNYA PADA SMK BINA INDUSTRI BEKASI - Zaenudin, M; Saleh, YKP; Sunardi, Ade; Nugraha, Dian; Faizah, Safira; Gamayel, Adhes; Hamzah, Kamal; Haryudiniarti, AN (Jurnal Abdi Insani, 2024)
The development of technology demands prospective workers to possess operational skills for equipment in industries, one of which relies on automation. A widely used example of automation technology in the industrial world is Programmable Logic Control (PLC), enabling the automatic control of industrial equipment with ease of scalability. In this context, vocational high school (SMK) students, representing a talent pool for the industrial sector, are required to understand, apply, and possess skills in operating PLC-based industrial equipment. However, to impart such skills, schools often face challenges in acquiring practical equipment, where the costs of which tend to be relatively high. In this community service (Abdimas) program, the team develops demonstration tools for industrial automation, specifically focusing on pneumatic actuators based on PLC. The partner and target in this community service program is SMK Bina Industri located in Ds. Jatiwangi, Kec. Cikarang Barat, Kab. Bekasi. The implementation of this program is carried out through several stages, including (1) identification of partner’s needs; (2) development of demonstration tools; (3) training on the use of demonstration tools; and (4) the handover of the demonstration tools. SMK Bina Industri highly appreciates the implemented program and encourages the development of a partnership that goes beyond the focus on developing demonstration tools and grants. It is expected to include capacity-building activities such as seminars/workshops for teachers and students. This program has successfully developed economical yet effective demonstration tools, opening opportunities for partnerships between universities and vocational high schools in embracing the Golden Indonesia's vision of 2045.